Communicating Ideal Social Institution: A Reading of Francis Bacon’s Of Judicature - Singh , Alka (IJLHE: International Journal of Language, Humanities, and Education, 2025)
Francis Bacon's essay "Of Judicature" is a probe into valuable insights regarding the office of a judge and the concept of justice. Bacon emphasizes the importance of judges being knowledgeable, impartial, and courageous in their decision-making. They should possess a deep understanding of the law and its applications. He considers a Judge’s position as a reasonable centre holding the faith and trust of the people in a society. Judges play a crucial role in upholding justice and ensuring that the legal system functions fairly and efficiently. Bacon stresses the need for judges to maintain their integrity and independence, avoiding external influences and personal biases. The Essay “Of Judicature”, views justice as a fundamental principle of society, which is essential for maintaining order and stability, where he highlights the importance of justice. The present paper offers a reading of Bacon’s ‘Of Judicature’ in understanding the Office of Judges as an important social institution in guiding the people to opt for the right action on the right path and constructively strengthening the human psychology in institutionalizing faith and trust of the people in the legal system.